Pengaruh Risiko Pembiayaan Mudharabah dan Musyarakah terhadap Profitabilitas Bank Syariah Bukopin - Murni Hayati; Dona Kurnia; Efmi Maiyana (Politeknik Negeri Padang, 2022)
The objective of this research to test the influence of Mudharabah and Musyarakah Financing Risks on Profitability of Sharia Bank Bukopin. Samples were Financial Statements of Sharia Bank Bukopin listed BEI period 2017 until 2021. Variable in this research are Mudharabah and Musyarakah Financing Risks as independen variable and Profitability as dependen variable. Measured of Mudharabah Financing Risks variable used Non Performing Financing (NPF_Mudharabah Financing Risks). Measured of Musyarakah Financing Risks variable used Non Performing Financing (NPF_Musyarakah Financing Risks). Whereas Measured of Value Profitability variable used Return on Assets (ROA).The regression model explores the relationship between Mudharabah Financing Risk and Musyarakah Financing Risk and its contribution to the Profitability of Sharia Bank Bukopin. The result reveal that Mudharabah Financing Risk effected nagatively and insignificant to Profitability, Musyarakah Financing Risk effected nagatively and insignificant to Profitability, as well as Mudharabah and Musyarakah Financing Risks effected nagatively and insignificant to Profitability of of Sharia Bank Bukopin.